Occurrence of Fasciola hepatica (Linnaeus, 1758) infection in Brazilian cattle of Minas Gerais, Brazil - Lima,Walter dos Santos (2009)
Fasciolosis is a parasitic disease which is caused by digenetic trematodes, such as Fasciola hepatica, and which occurs worldwide. The disease causes significant economic losses in cattle because of the reduction in milk and meat production and because the parasitized livers have no economic value. Also, abortion and mortality rates increase. To determine the occurrence and dispersal of F. hepatica in the state of Minas Gerais, fecal samples were collected from bovines aged 12 months and older between April 2005 and April 2006. The bovines came from 1,251 rural farms of 120 municipalities/cities in Minas Gerais. Water was collected to ascertain the presence of the intermediate host in the properties where infected bovines were found. A total of 16 municipalities had infected bovines and 13 had the presence of Lymnaea columella. We detected infected bovines in 70% of the rural farms visited in the municipality of Itajubá. Itajubá was also found to have infected snails with the larval stage of F. hepatica. The results revealed that infection by F. hepatica in bovines of Minas Gerais was associated with the presence of the intermediate host and favorable epidemiological factors, drawing attention to the necessity of adopting proper control measures in the area.